Система управління персоналом підприємства: шляхи удосконалення - Петрик, Юлія Сергіївна; Михайленко, Ольга Валеріївна (My University, 2020)
У статті на підставі визначеної сутності персоналу виявлено основні тенденції та напрями його вдосконалення, що обумовлено недостатнім рівнем кваліфікації та наявної кадрової політики, яка спричиняє неспроможність підприємства успішно проводити свою діяльність у різних нестабільних економічних умовах. Задля вдосконалення управління трудовими ресурсами визначено певні цілі компанії (з розподілом на категорії), виокремлено декілька шляхів ефективного управління трудовими ресурсами. Визначено особливості управління персоналом з урахуванням особистих властивостей працівників (забезпечення росту їх кваліфікаційного та професійного рівня, підтримка відвідування професійних груп, де успішні професіонали в певній ділянці роботи діляться власним досвідом та секретами успіху). Отже, на основі персоналізму для дотримання потрібного рівня управління персоналом необхідно не лише постійно підтримувати, але й періодично покращувати умови роботи та її безпеку, надавати відповідне сучасне обладнання для покращення й пришвидшення виконання роботи тощо. Запропоновано надання гнучкого або вільного графіку роботи, введення таких стимулів для підвищення роботи, як моральні та матеріальні, постійний контроль підвищення кваліфікаційного рівня співробітників як заходи покращення використання персоналу підприємства. The article, based on the defined essence of personnel, reveals the main trends and directions of its improvement due to insufficient qualifications and existing personnel policy, which causes the inability of the company to successfully conduct its activities in various unstable economic conditions. In order to improve human resource management, certain goals of the company (divided into categories) are identified, and several ways of effective human resource management are identified. The article identifies the features of personnel management taking into account the personal characteristics of employees (ensuring the growth of their qualifications and professional level, supporting visits to professional groups, where successful professionals in a particular field of work, share their own experience and secrets of success, etc.). That is, on the basis of personalize, in order to comply with the required level of personnel management, it is necessary not only to constantly maintain but also periodically improve working conditions and safety, provide appropriate modern equipment to improve and accelerate performance, and so on. The paper proposes the provision of a flexible or free work schedule, the introduction of incentives to improve work as moral and material, constant monitoring of staff development, as measures to improve the use of staff. The article considers the concept of effective personnel management, which is the main reserve for the growth of industrial production. The development of a mechanism for effective personnel management of enterprises to ensure the effectiveness of work in the long run, which will create new conditions for development and increase their competitiveness. The improvement of the enterprise’s work and its competitiveness with the help of labor resources is also considered. Since labor resources are the main resources of the enterprise, their implementation is the main purpose of the enterprise. The article considers the opinions and views of various scientific papers and scientists on the use of labor resources and ways to improve them, which in turn leads to improved performance of the enterprise.
Keywords: удосконалення; управління персоналом; ефективність; економіка; підприємство; покращення; ways of improvement; personnel management; efficiency; economy; enterprise; improvement; кафедра обліку і аудиту